2023
DOI: 10.1021/acs.analchem.3c00842
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Linear Ion-Trap Data-Independent Acquisition toward Single-Cell Proteomics

Abstract: A linear ion trap (LIT) is an affordable, robust mass spectrometer that provides fast scanning speed and high sensitivity, where its primary disadvantage is inferior mass accuracy compared to more commonly used time-of-flight or orbitrap (OT) mass analyzers. Previous efforts to utilize the LIT for low-input proteomics analysis still rely on either built-in OTs for collecting precursor data or OT-based library generation. Here, we demonstrate the potential versatility of the LIT for low-input proteomics as a st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…2B ). We also adopted this modification to linear ion trap (LIT) based DIA 37 39 and observed similar overall performance gains (Supplementary Fig. 3A–C ), although it did not surpass OT-based HRMS1-DIA.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…2B ). We also adopted this modification to linear ion trap (LIT) based DIA 37 39 and observed similar overall performance gains (Supplementary Fig. 3A–C ), although it did not surpass OT-based HRMS1-DIA.…”
Section: Resultsmentioning
confidence: 83%
“…This hints at heterogeneous glycolytic propensity of the identified m15 subcluster, potentially reflecting the extent to which cells have drifted from the embryonic-like state. Although the function of Eno1 in mESC has been recently explored 39 , the exact role of Pgam1 has not yet been investigated.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our lab demonstrated that LITs could effectively be used as stand-alone mass analyzers to measure low-input samples down to single cells using a Thermo Scientific™ Orbitrap Eclipse™ Tribrid™ mass spectrometer. 22 In that work, we detected approximately 400 proteins from single cells using data-independent acquisition coupled with chromatogram library generation to help make detections. 28 While the Eclipse instrument configuration ignored the high-resolution Orbitrap mass analyzer, we performed those experiments in the context of a high-end Tribrid instrument.…”
Section: Resultsmentioning
confidence: 99%
“…20 In some circumstances, LITs can be more effective than high-resolution mass analyzers for lowinput samples (≤10 ng) 21 and are capable of measuring single cells without multiplexing reagents. 22 At higher sample input (≥100 ng) the sensitivity of LITs is overshadowed by the lack of high mass accuracy. There exist other compelling reasons to consider LIT-based instruments in high-throughput applications.…”
Section: Introductionmentioning
confidence: 99%
“…The CHIMERYS software has become recently available through Proteome Discoverer and is now compatible with phosphoproteomics and DIA work flows. DIA using LIT mass analysis has also been investigated, , and narrow-DIA bins (∼4 m / z windows with overlapping acquisitions for effective 2 m / z bins) on fast scanning instruments, e.g., the Orbitrap Astral MS discussed above, are blurring the lines between DDA and DIA acquisitions schemes.…”
Section: Ms-centric Technology Used In Modern Proteomicsmentioning
confidence: 99%